Click, Trust and Stay: What Keeps Indonesians Using Digital-Only Banking? - Ambarwati, Dian; Widjaya, Satrya; Tanjung , Miranda Hotmadia (Jurnal Locus Penelitian dan Pengabdian, 2025)
This Study Investigates The Factors That Influence Users' Intention To Continue Using Digital Banking Services In Indonesia, Focusing On Fully Digital Banks Without Branches Such As Blu By Bca Digital, Jenius, Seabank And Others. Based On The Technology Continuance Theory (Tct), This Study Integrates The Main Constructs Of The Technology Acceptance Model (Tam) And The Expectation Confirmation Model (Ecm) And Extends The Framework By Including Two Important Factors In The Context Of Digital Finance, Namely Trust And Perceived Risk. Data Were Collected Through A Structured Online Questionnaire, Resulting In 227 Valid Responses From Active Digital Banking Users. Partial Least Squares Structural Equation Modeling (Pls-Sem) Was Employed To Test Eight Hypotheses Involving Confirmation, Perceived Ease Of Use, Perceived Usefulness, Satisfaction, Attitude Toward The Service, Trust And Perceived Risk. The Results Revealed That Confirmation And Perceived Ease Of Use Significantly Influenced Perceived Usefulness, Which In Turn Had A Strong Impact On User Satisfaction. Furthermore, Satisfaction Improved User Attitudes Toward The Service. However, The Direct Effects Of Satisfaction, Attitude, Trust, And Perceived Risk On Continuance Intention Were Found To Be Statistically Insignificant, Indicating Potential Indirect Pathways Or Conceptual Overlap. Discriminant Validity Issues Identified Through Htmt Analysis Indicated High Intercorrelations Among These Constructs, Warranting Further Refinement In Future Models. This Study Contributes To The Post-Adoption Literature By Validating An Extended Tct Model In The Context Of Indonesian Digital Banking. It Offers Practical Recommendations For Digital Banks To Focus On Functional Value And User Experience Rather Than Solely Emphasizing Trust-Building Or Risk Reduction. Future Research Should Address The Model’s Limitations By Including Moderating Variables, Using Longitudinal Data And Expanding To Cross-National Contexts.